NcSWP8, a New Spore Wall Protein, Interacts with Polar Tube Proteins in the Parasitic Microsporidia Vairimorpha (Nosema) ceranae - Pengfei Wang; Dufu Li; Qianmin Hai; Siming Liu; Yueyue Zhang; Jun Zhang; Jinshan Xu; Zhengang Ma; Zeyang Zhou (Microorganisms, 2025)
Vairimorpha (Nosema) ceranae is a pathogen that affects Apis mellifera and Apis ceranae Fabricius, capable of spreading within and between honeybee colonies. The spore wall of microsporidia is the initial structure to contact the host cell directly, which may play a crucial role in the infection process. Currently, several spore wall proteins have been identified in microsporidia, but only two spore wall proteins from V. ceranae have been characterized. Here, we report the expression and identification of a novel spore wall protein, NcSWP8, with a molecular mass of 21.37 kDa in V. ceranae. Subcellular localization analysis revealed that NcSWP8 was localized on the spore wall of V. ceranae. Co-immunoprecipitation and Far-Western blotting experiments demonstrated that NcSWP8 could stably interact with polar tube proteins, NcPTP2 and NcPTP3. The antibody blocking assay significantly decreased their infection rate, indicating that NcSWP8 played a significant role in the process of V. ceranae infection. These results together suggested that NcSWP8 was a new spore wall protein localized to the spore wall and interacted with the polar tube proteins, playing a crucial role in supporting the formation of the spore wall and potentially affecting the process of infection of V. ceranae.